Deficits in the Proline-Rich Synapse-Associated Shank3 Protein in Multiple Neuropsychiatric Disorders - Alexandrov, Peter N.; Zhao, Yuhai; Jaber, Vivian; Cong, Lin; Lukiw, Walter J. (Frontiers in Neurology, 2017)
Signaling between neurons in the human central nervous system (CNS) is accomplished through a highly interconnected network of pre-synaptic and post-synaptic elements essential in the conveyance of electrical and neurochemical information. One recently characterized core post-synaptic element essential to the efficient operation of this complex network is a relatively abundant ~184.7 kDa proline-rich synapse-associated cytoskeletal protein known as Shank3 (SH3-ankyrin repeat domain; encoded at human chr 22q13.33). In this’Perspectives’ paper we review and comment on current advances in Shank3 research and include some original data that shows common Shank3 deficits in a number of seemingly unrelated human neurological disorders that include sporadic Alzheimer’s disease (AD), autism-spectrum-disorder (ASD), bipolar-disorder (BD), Phelan-McDermid-syndrome (PMS; 22q13.3 deletion syndrome), and schizophrenia (SZ). Shank3 was also found to be down-regulated in the CNS of the transgenic AD (TgAD) 5XFAD murine model engineered to over-express the 42 amino-acid amyloid-beta (Aβ42) peptide. Interestingly, the application of known pro-inflammatory stressors, such as the Aβ42-peptide and the metal-neurotoxin aluminum sulfate to human neuronal-glial (HNG) cells in primary culture resulted in a significant decrease in the expression of Shank3. These data indicate that deficits in Shank3-expression may be one common denominator linking a wide-range of human neurological disorders that exhibit a progressive or developmental synaptic disorganization that is temporally associated with cognitive decline.